The Economic Viability of Regenerative Agriculture: A Systematic Review from a Cost-Benefit Analysis Perspective - Chanra Simamora; Safta Junita (CV. Get Press Indonesia, 2025)
This study evaluates the long-term economic viability of regenerative agriculture in rural areas using a comprehensive Cost-Benefit Analysis (CBA). The findings reveal that despite initial investments, these practices yield significant financial returns alongside positive social and environmental impacts, including improved farmer welfare and enhanced soil health. The results highlight regenerative agriculture as a resilient strategy that requires supportive policies for widespread adoption. Importantly, future research should leverage advanced technologies such as big data and AI, which can improve predictive accuracy, integrate diverse datasets, and enable real-time monitoring of ecological and economic dynamics, thereby strengthening evidence-based decision-making for sustainable and resilient rural food systems.